Seasonal incidence of cellulitis in cystic lymphatic malformation and Klippel–Trenaunay syndrome - Tamotsu Kobayashi; Akihiro Fujino; Ryoya Furugane; Naoki Hashizume; Teizaburo Mori; Motohiro Kano; Eiichiro Watanabe; Masataka Takahashi; Akihiro Yoneda; Yutaka Kanamori (Global Pediatrics, 2023)
Background: Cellulitis is a common complication of cystic lymphatic malformations (cLM) and Klippel–Trenaunay syndrome (KTS). Cellulitis in the pediatric population requires hospitalization and reduces a patients’ quality of life. This study aimed to clarify the seasonality and characteristics of cellulitis in patients with cLM and KTS. Methods: We retrospectively reviewed the clinical records of patients with cLM and KTS who were admitted for cellulitis between January 2014 and December 2021. Results: One hundred and seventeen hospitalizations of 33 patients with cellulitis were examined. There were 80 and 37 hospitalizations for cLM and KTS oatients, respectively. The number and percentage of hospitalizations in spring, summer, autumn, and winter were 26 (22.2%), 43 (36.8%), 19 (16.2%), and 29 (24.8%), respectively, showing a significantly different frequency (P = 0.018). The number of hospitalization days per season was not significantly different between the seasons (P = 0.335). Seasonality and hospitalization duration did not differ significantly between the cLM and KTS groups. Of the 117 hospitalized cases, only 5 (4.3%) had positive blood cultures. The number of hospitalizations remarkably correlated with temperature and humidity from April to November. Conclusions: Cellulitis associated with lymphatic malformations, such as cLM and KTS, occurs more frequently in the summer. Patients should take precautions to prevent their lesions from progressing to cellulitis, particularly in summer. Levels of evidence: Level Ⅲ